A pilot case series of a brief acceptance and commitment therapy (ACT)-based guided self-help intervention for improving quality of life and mood in muscle disorders. (8th June 2017) - Graham, Christopher D.; Chalder, Trudie; Rose, Michael R.; Gavriloff, Dimitri; McCracken, Lance M.; Weinman, John
Abstract: This study aimed to demonstrate proof of concept and acceptability of a brief acceptance and commitment therapy (ACT)-based guided self-help intervention for improving quality of life (QoL) and mood for people with muscle disorders (MD). A case-series with an AB design was used to assess changes in primary (QoL) and secondary (depression and anxiety) outcome variables across the period of study. Change in the psychological process targeted by ACT – psychological flexibility – was also investigated, to allow insight into possible treatment mechanisms. Post-intervention, participants also completed a brief free-text evaluation. Relative to pre-intervention scores, four (of seven) participants showed varying degrees of improvement in all primary and secondary outcome variables and were thus considered responders. However, consistent concomitant improvements in psychological flexibility were not apparent. Participants reported a mostly positive experience of the intervention; all appeared to complete the intervention, and no adverse events were reported. Nonetheless, there was evidence that those with compromised concentration or who report good initial QoL and low levels of distress may derive less benefit. Although several methodological weaknesses limit the strength of our conclusions, this ACT-based guided self-help intervention shows encouraging utility for improving QoL and mood in MD.